Pengelolaan Media Sosial Instagram Pada Program Off Air “Jak After School” - Qoirul Nisa; Laksmi Rachmaria (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
In the digital era, conventional media such as radio face significant challenges due to shifts in media consumption behavior, particularly among urban youth who prefer digital platforms and social media. Jak 101 FM has adapted by utilizing Instagram digital media in an off-air program titled “Jak After School” to reach a broader audience and build a positive image. This study examines the public relations strategy of Jak 101 FM in managing Instagram as part of promotion and image enhancement using descriptive qualitative methods and Chris Heuer's 4C theory (context, communication, collaboration, and connection). Research findings show that Jak 101 FM's public relations strategy involves creative content production, utilization of Instagram's interactive features, collaborating with local communities and influencers, and building emotional connections with audiences. The “Jak After School” program become an effective medium that strengthens audience loyalty and maintains Jak 101 FM's existence amid digital media industry competition.